2012
DOI: 10.1002/j.1875-9114.2012.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Disadvantages of Etomidate Use for Intubation of Patients with Sepsis

Abstract: Etomidate is a potent imidazole hypnotic used widely in single doses in the rapid sequence intubation of critically ill patients with sepsis due to its presumed hemodynamic safety, fast onset, and short duration of action. However, the literature is conflicting regarding the hemodynamic advantages of etomidate over other induction agents, and its safety in this population is a matter of strong debate in the critical care community as the drug is associated with suppression of adrenal steroidogenesis, which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…There is a relation between etomidate administration and adrenal insufficiency, which caused by reversible inhibition of cortisol synthesis ( 9 ). Reduced cortisol and aldosterone level following to adrenal suppression almost started in less than 30 minutes after a single dose of etomidate and can last up to 72 hours ( 10 ). On the other hand, it has been shown that relative adrenal insufficiency in septic patients may induce morbidity and mortality ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a relation between etomidate administration and adrenal insufficiency, which caused by reversible inhibition of cortisol synthesis ( 9 ). Reduced cortisol and aldosterone level following to adrenal suppression almost started in less than 30 minutes after a single dose of etomidate and can last up to 72 hours ( 10 ). On the other hand, it has been shown that relative adrenal insufficiency in septic patients may induce morbidity and mortality ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…7 The major side effect and concern in the use of etomidate is its ability to inhibit 11-b-hydroxylase, which decreases cortisol, aldosterone, and corticosterone, leading to adrenal suppression. 8,9 This suppression can last up to 72 hours after a single dose of etomidate. In fact, an adult who received a 20-hour infusion of etomidate (1.3-1.5 mg/kg/hr) had marked adrenocortical suppression that was evident 4 days after etomidate was discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…Patienten mit Sepsis, die bereits eine gestörte Nebennierenrindenfunktion aufweisen können, sind dabei besonders gefährdet. Beim geringsten Anzeichen einer septischen Konstellation ist daher von jeglichem Gebrauch dringend abzuraten [11].…”
Section: Kardiopulmonale Belastbarkeitunclassified